Identification and characterization of two bisabolene synthases from linear glandular trichomes of sunflower (Helianthus annuus L., Asteraceae). (April 2016) - Aschenbrenner, Anna-Katharina; Kwon, Moonhyuk; Conrad, Jürgen; Ro, Dae-Kyun; Spring, Otmar
Graphical abstract: Two enzymes using farnesyldiphosphate to form ( Z )-γ-bisabolene were identified from the RNA pool of sunflower trichomes and characterized by heterologous expression in yeast. Highlights: This is the first identification of a bisabolene synthase from Asteraceae. Cellular localization was identified by gene expression in RNA pool of trichomes. The enzyme produces a singular product from farnesyldiphosphate. The product was characterized as ( Z )-γ-bisabolene by 2D- 1 H-NMR experiments. Sequence comparison indicated origin from Asteracean β-farnesene synthases. Abstract: Sunflower is known to produce a variety of bisabolene-type sesquiterpenes and accumulates these substances in trichomes of leaves, stems and flowering parts. A bioinformatics approach was used to identify the enzyme responsible for the initial step in the biosynthesis of these compounds from its precursor farnesyl pyrophosphate. Based on sequence similarity with a known bisabolene synthases from Arabidopsis thaliana AtTPS12, candidate genes of Helianthus were searched in EST-database and used to design specific primers. PCR experiments identified two candidates in the RNA pool of linear glandular trichomes of sunflower. Their sequences contained the typical motifs of sesquiterpene synthases and their expression in yeast functionally characterized them as bisabolene synthases. Spectroscopic analysis identified the stereochemistry of the product of both enzymes as ( Z )-γ-bisabolene. The origin of the two sunflower bisabolene synthase genes from the transcripts of linear trichomes indicates that they may be involved in the synthesis of sesquiterpenes produced in these trichomes. Comparison of the amino acid sequences of the sunflower bisabolene synthases showed high similarity with sesquiterpene synthases from other Asteracean species and indicated putative evolutionary origin from a β-farnesene synthase.